Climbing the Ladder : Poverty Reduction and Shared Prosperity in Vietnam - World Bank (World Bank, Washington, DC, 2018)
Vietnam has achieved remarkable success in reducing poverty while controlling inequality. The country’s broad-based growth reflects the government’s focus on developing labor-intensive export sectors while investing heavily in human capital that saw the country exceed its peers. However, gains have been concentrated among the Kinh and Hoa ethnic majority, while minority groups have not only continued to experience poverty rates far above the national average, but have seen slower progress too. This report analyzes recent trends in poverty and shared prosperity. It presents the findings of the 2016 Vietnam household and living standards survey (VHLSS), highlighting important progress and identifying new challenges. The report is organized into two main sections. The first section reviews Vietnam’s progress in reducing poverty and promoting share prosperity. It describes updated poverty and shared prosperity trends, the nature of economic mobility, and the drivers of poverty reduction. The second section – titled leaving no one behind is more forward-looking, starting by identifying major constraints faced by the poor, then proceeding to lay out challenges for moving the poverty and shared prosperity agenda going forward.